Consensus views on an advanced breast cancer education curriculum for cancer nurses: A Delphi study. (May 2023) - Drury, Amanda; de Los Rios la Serna, Celia Diez; Bağçivan, Gülcan; Dowling, Maura; Kotronoulas, Grigorios; Shewbridge, Amanda; Sheehan, Sarah; Erdem, Sema; Aroyo, Violet; Wiseman, Theresa
Abstract: Background: Specialist nursing care is a core indicator of quality care for people living with advanced breast cancer. However, access to and quality of nurse education programmes in advanced breast cancer is variable. Objectives: This study aims to define the topics for inclusion in an international curriculum for an advanced breast cancer education programme. Methods: A modified four-round Delphi study was undertaken with experts by profession and experience in advanced breast cancer. Thirty-four topics related to advanced breast cancer and six online teaching and learning methods were pre-selected following a systematic review. Between September 2021 and March 2022, the expert panel determined the importance of topics for inclusion in the education programme. Consensus was defined by at least 80 % agreement on the highest three points on a 9-point Likert scale. Results: A total of 31 experts participated in rounds 1–3 of this study, and 156 experts by profession and experience participated in an additional fourth round, including people living with advanced breast cancer ( n  = 72, 46 %), healthcare professionals ( n  = 46, 29 %), family members or caregivers of a person diagnosed with advanced breast cancer ( n  = 30, 19 %) and advocacy professionals working in the area of advanced breast cancer ( n  = 8, 5 %). In round 4, 36 topics and five of six learning methods reached consensus. Conclusions: The results of this study provide a framework to develop education programmes in advanced breast cancer, defining the essential elements of curriculum content for such programmes. The results highlight the need for advanced breast cancer education programmes to use multiple teaching and learning methods to promote nurses' understanding of person-centred supportive care and the physical, psychosocial and spiritual issues experienced by people living with advanced breast cancer.